Assessment of plasma resolvin levels in women with breast cancer and their associations with disease presentation and immunohistochemical characteristics - Alessio Molfino; Giovanni Imbimbo; Gerardo Salerno; Luana Lionetto; Alessandro De Luca; Maria Ludovica Costanzo; Maurizio Simmaco; Maurizio Muscaritoli; Maria Ida Amabile (Lipids in Health and Disease)
Abstract Background Resolvins, which are divided into series D (RvD) and E (RvE), originate from omega-3 fatty acids, DHA and EPA and were recently found to be involved in the modulation of inflammation in some tumors, including breast cancer (BC). We aimed to assess the resolvin profiles (RvD1, RvD2, RvD3 and RvE1) in the plasma of BC patients compared with those of controls and to determine differences in their concentrations according to BC presentation and immunohistochemical characteristics. Methods We considered BC patients (sporadic, familiar and BRCA1/2-mutated forms) naïve to any anticancer treatment and controls affected by nonmalignant breast disease. According to the BC immunohistochemical characteristics, we identified the luminal-A, luminal-B, HER2 + and triple-negative subtypes. The levels of RvD1, RvD2, RvD3 and RvE1 in the plasma of all the participants were measured via ELISA kits. Results We enrolled 64 women, 53 with BC (age 51 ± 10 y) and 11 controls (age 49 ± 7 y). Twenty-seven patients presented with sporadic BC, 16 with a positive history of BC (familiar), and 10 with BRCA 1/2 gene mutations. Compared with control patients, BC patients presented higher levels of RvD1 (p = 0.015), and no differences were detected for RvD2, 3 or RvE1. In BC, all resolvin levels were positively correlated with each other (p < 0.001). The expression of RvD1 and RvD3 was lower in the mutated group than in the familiar and sporadic groups (p < 0.05). The expression of RvD2 and RvE1 tended to be lower in the BRCA 1/2-mutated group than in the sporadic and familiar BC patients (p = 0.051 and p = 0.062, respectively). No differences in plasma resolvin levels were observed according to immunohistochemical characteristics (luminal A, luminal B, HER2+, triple-negative). However, RvD1 was lower in triple-negative patients than in patients with the other BC subtypes (p = 0.023). In terms of Ki-67 expression, RvD3 expression was lower in patients with high Ki-67 expression ( $$\:\ge\:$$ 20%) than in those with low Ki-67 expression (<20%) (p = 0.034). Conclusion This is the first human study profiling specific plasma resolvin levels in BC patients, which revealed low plasma levels of some resolvins in patients with BRCA1/2 mutations, triple-negative subtypes and high Ki-67 expression, potentially impacting treatment response and prognosis.